Human Radiation Dosimetry for Orally and Intravenously Administered 18F-FDG - Srinivasan, Senthamizhchelvan; Crandall, John P; Gajwani, Prateek; Sgouros, George; Mena, Esther; Lodge, Martin A; Wahl, Richard L (The Journal of nuclear medicine (1978), 2020)
Intravenous access is difficult in some patients referred for 18F-FDG PET imaging. Extravasation at the injection site and accumulation in central catheters can lead to limited tumor 18F-FDG uptake, erroneous quantitation, and significant image artifacts. In this study, we compared the human biodistribution and dosimetry for 18F-FDG after oral and intravenous administrations sequentially in the same subjects to ascertain the dosimetry and potential suitability of orally administered 18F-FDG as an alternative to intravenous administration. We also compared our detailed intravenous 18F-FDG dosimetry with older dosimetry data. Methods: Nine healthy volunteers (6 male and 3 female; aged 19–32 y) underwent PET/CT imaging after oral and intravenous administration of 18F-FDG. Identical preparation and imaging protocols (except administration route) were used for oral and intravenous studies. During each imaging session, 9 whole-body PET scans were obtained at 5, 10, 20, 30, 40, 50, 60, 120, and 240 min after 18F-FDG administration (370 ± 16 MBq). Source organ contours drawn using CT were overlaid onto registered PET images to extract time–activity curves. Time-integrated activity coefficients derived from time–activity curves were given as input to OLINDA/EXM for dose calculations. Results: Blood uptake after orally administered 18F-FDG peaked at 45–50 min after ingestion. The oral-to-intravenous ratios of 18F-FDG uptake for major organs at 45 min were 1.07 ± 0.24 for blood, 0.94 ± 0.39 for heart wall, 0.47 ± 0.12 for brain, 1.25 ± 0.18 for liver, and 0.84 ± 0.24 for kidneys. The highest organ-absorbed doses (μGy/MBq) after oral 18F-FDG administration were observed for urinary bladder (75.9 ± 17.2), stomach (48.4 ± 14.3), and brain (29.4 ± 5.1), and the effective dose was significantly higher (20%) than after intravenous administration (P = 0.002). Conclusion: 18F-FDG has excellent bioavailability after oral administration, but peak organ activities occur later than after intravenous injection. These data suggest PET at 2 h after oral 18F-FDG administration should yield images that are comparable in biodistribution to conventional clinical images acquired 1 h after injection. Oral 18F-FDG is a palatable alternative to intravenous 18F-FDG when venous access is problematic.